TMS2015 Supplemental Proceedings 2015
DOI: 10.1002/9781119093466.ch55
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Deformation Processing with Additive Manufacture of Ti‐6A1‐4V Components for Improved β Grain Structure and Texture

Abstract: With Ti alloys like Ti-6Al-4V, the solidification conditions across virtually all AM platforms lead to strongly textured, coarse columnar, β grain structures. Transformation to α on cooling dilutes the texture, but significant texture is still inherited which contributes to undesirable anisotropy in AM parts. In the work presented a deformation step has been integrated into the manufacture of components produced by the blown powder method, using an Ultrasonic Impact Treatment (UIT), which has the additional be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…When rolling was applied, new β orientations, associated with the deformation of α laths, were created and a strong columnar texture was mitigated. In a recent study, these new β orientations were found to arise from twinning with the residual β [52]. Another key effect observed was the refinement effect induced by the interpass rolling applied to the WAAM deposits: by increasing the applied load the grains become more refined, resulting in an improvement of the material microstructure.…”
Section: Methodsmentioning
confidence: 99%
“…When rolling was applied, new β orientations, associated with the deformation of α laths, were created and a strong columnar texture was mitigated. In a recent study, these new β orientations were found to arise from twinning with the residual β [52]. Another key effect observed was the refinement effect induced by the interpass rolling applied to the WAAM deposits: by increasing the applied load the grains become more refined, resulting in an improvement of the material microstructure.…”
Section: Methodsmentioning
confidence: 99%
“…Zhi et al studied the influence of ultrasonic shock on the mechanical properties of arc-added titanium alloy parts. As shown in Figure 18 , ultrasonic shock can reduce the anisotropy of mechanical properties of parts, and the percentage of anisotropy in tensile strength of parts was 12.5%, reduced by 1.5% [ 79 ].…”
Section: Current Methods For Quality Improvement In the Waam Procementioning
confidence: 99%
“…Zhi et al studied the influence of ultrasonic shock on the mechanical properties of arc-added titanium alloy parts. As shown in Figure 18, ultrasonic shock can reduce the anisotropy of mechanical properties of parts, and the percentage of anisotropy in tensile strength of parts was 12.5%, reduced by 1.5% [79]. Donoghue et al studied the effect of ultrasonic shock on the microstructure of arcadded TC4 titanium alloy, and found that ultrasonic shock can break coarse columnar crystals and form fine equiaxed crystal structures.…”
Section: Peening and Ultrasonic Impact Treatmentmentioning
confidence: 99%
“…The optimization of having an accurately fitting part can have profound impacts on specific fit-for-purpose operations. One example can be shown in Donoghue [47] and his investigation of hybrid additive manufacturing techniques for aerospace-based components. In his example, he elaborates on the use of bearings for aerospace-based applications.…”
Section: The Importance Of Tribological Property Alterations In Addit...mentioning
confidence: 99%